Development and Planning in Seven Major Coastal Cities in Southern and Eastern China - Shen, Jianfa; Kee, Gordon (Springer International Publishing : Imprint: Springer, 2017)
This book analyzes the recent growth of Guangzhou, Shenzhen, Fuzhou, Shanghai, Hangzhou, Nanjing, and Hong Kong, seven major Chinese coastal cities. The authors detail theoretical mechanisms, spatial and non-spatial models of development, all while exploring possible directions to sustainability. They also look at how these cities have developed over the last 30 years, from the late 1970s to the 21st century. Each has its own unique background, regional and national positions, advantages, and functions. Using diversified approaches and measurements for each city, the authors argue that structural changes are necessary to achieve much needed sustainable development. The book covers developmental issues such as the regaining of central city and global city statuses, the role of governments in steering development, and achieving goals through mega projects, urban competitiveness, positioning, and branding. Including varied assessment and intense suggestions for structural changes, this book addresses core concerns for the sustainable growth of these metropolises. A valuable book for students, researchers and policy makers.
Keywords: Social sciences.; Economic geography.; Urban geography.; Sociology, Urban.; Human geography.; elektronické knihy; electronic books